Anesthetic injections and analgesia use in pediatric post-tonsillectomy patients: A meta-analysis and systematic review. (January 2022) - Ortega, Briana; Stramiello, Joshua A.; Brigger, Matthew; Nation, Javan
Abstract: Objective: To assess the effect of local anesthetic injection on post-operative analgesia and complications for pediatric tonsillectomies on post-operative day (POD) 0 and 1. Methods: A 2-researcher team following the PRISMA guidelines performed a systematic review and meta-analysis. The databases Pubmed.gov, Embase, Web of Science, and Scopus were used. Studies written with original data utilizing a saline injection control arm were selected. Corresponding authors were contacted for missing data, which was used when possible. The collated data was analyzed with Review Manager (RevMan) Version 5.4., The Cochrane Collaboration, 2020. Surgical technique subgroup analysis was performed. Results: 319 publications were identified and 8 articles with 12 total experimental arms (529 participants) were selected. Local anesthetic injection was compared to saline injection. The standard mean difference for time until first analgesic was 0.68 min [0.26, 1.09](P = 0.001) in favor of local anesthetic. The odds ratio (OR) for patients receiving one or more narcotic doses on POD 0 was 0.22 [0.06, 0.84](P = 0.03) in favor of local anesthetic. Conclusions: Use of an intraoperative anesthetic injection during pediatric tonsillectomy can help improve initial recovery as it delays the need for narcotic medication and may reduce postoperative narcotic usage on POD 0 and 1. In addition, a local anesthetic does not increase the risk of postoperative bleeding or dehydration.